Flexural creep behavior in utilization of woven glass-fibre as reinforcement in pultruded glass fibre-reinforced polymer composite cross-arms: experimental and numerical analysis - Amir, A.L.; Yamunan, S.; Ishak, M.R.; Yidris, N.; Zuhri, M.Y.M. (EDP Sciences, 2024)
Pultruded glass fiber-reinforced polymer (PGFRP) composite is a relatively new material used to replace conventional wood in the fabrication of cross-arms for transmission towers. Much research has been undertaken on coupon-scale PGFRP composite cross-arms. However, a few have been completed on full-scale PGFRP composite cross-arms under actual operating load. Thus, this work investigates the effect of wrapping woven glass fiber fabric as an additional reinforcement on the creep reactions of PGFRP composite cross-arms installed in a 132 kV transmission tower. In the first stage of this research, the deflection of the original cross-arm under various loads ranging from 0 to 9 kN was evaluated and was followed by the actual working loads. This experiment was repeated on cross-arms wrapped with different numbers of glass fiber fabric layers around the weakest point of the beam. Then, the creep behaviors and responses of the woven glass fiber- reinforced cross-arms were evaluated and compared with the original cross-arms from the previous study. The actual operating load was applied to the PGFRP composite cross-arms for 1000 hours to study their capability to support the weight of electrical cables and insulators. In order to replicate the tropical climate, the cross-arm were mounted on a test rig in an open area. The findings of this study revealed that reinforcing the cross-arm by wrapping it with woven glass fiber fabric could extend its life and hence reduce the maintenance cost and effort for long-term usage. The finding of this study will also become essential knowledge on woven fabric wrapping applications on square profiles.